Stunting and Associated Factors among Under-Five-Age Children in West Guji Zone, Oromia, Ethiopia - Eyob Afework; Selamawit Mengesha; Demelash Wachamo (Journal of Nutrition and Metabolism)
Background. Stunting is one of the most important public health problems in Ethiopia. It remains a problem of greater magnitude particularly in rural and low-income areas. It reflects chronic nutritional deficiencies and illness that occur during the most critical periods for growth and development in early life. It needs proper intervention to save the future, unless it resulted in diminished cognitive and physical development for the rest of their lives. Therefore, this study aimed to assess the prevalence of stunting and associated factors among under-five children in West Guji Zone, Oromia, Ethiopia. Method. A community-based cross-sectional study was conducted among 767 under-five children who were included in this study by using a multistage sampling technique in 12 kebeles from 3 selected districts. Data were collected from a mother/caregiver of the child by using a structured pretested questionnaire. Standardized anthropometric measurements were used to measure length, weight, and height of a child. Data were entered into Epi Info software version 3.5.1 and exported to SPSS version 23 for analysis for descriptive and logistic regression models. Result. The prevalence of stunting was 244 (31.8%) with 95% CI (28.6–35.2) among under-five-age children. The under-five children whose fathers had a polygamous marriage (AOR = 4.92, 95% CI: 3.46, 7.00), being female sex (AOR = 1.74, 95% CI: 1.23, 2.47), having below 4 meal frequencies (AOR = 2.95, 95% CI: 1.56, 5.58), not vaccinated (AOR = 1.75, 95% CI: 1.15, 2.67), and from poor households’ wealth status (AOR = 3.03, 95% CI: 1.63, 5.63) and also from severely food insecure household (AOR = 2.92, 95% CI: 1.36, 6.24) were short for their age compared with their counterparts. Conclusion. Nearly one-third of the under-five children were stunted in the study area which needs intervention on child-feeding practice to avoid sex discrimination in the community. In addition to this health officials in collaboration with other sectors, it is needed to act together to improve enforcement of the law for polygamous marriage, the household’s wealth status, and food security for the better health of a child and future.